(a+2)(a-5)(a+3)=

Simple and best practice solution for (a+2)(a-5)(a+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a+2)(a-5)(a+3)= equation:


Simplifying
(a + 2)(a + -5)(a + 3) = 0

Reorder the terms:
(2 + a)(a + -5)(a + 3) = 0

Reorder the terms:
(2 + a)(-5 + a)(a + 3) = 0

Reorder the terms:
(2 + a)(-5 + a)(3 + a) = 0

Multiply (2 + a) * (-5 + a)
(2(-5 + a) + a(-5 + a))(3 + a) = 0
((-5 * 2 + a * 2) + a(-5 + a))(3 + a) = 0
((-10 + 2a) + a(-5 + a))(3 + a) = 0
(-10 + 2a + (-5 * a + a * a))(3 + a) = 0
(-10 + 2a + (-5a + a2))(3 + a) = 0

Combine like terms: 2a + -5a = -3a
(-10 + -3a + a2)(3 + a) = 0

Multiply (-10 + -3a + a2) * (3 + a)
(-10(3 + a) + -3a * (3 + a) + a2(3 + a)) = 0
((3 * -10 + a * -10) + -3a * (3 + a) + a2(3 + a)) = 0
((-30 + -10a) + -3a * (3 + a) + a2(3 + a)) = 0
(-30 + -10a + (3 * -3a + a * -3a) + a2(3 + a)) = 0
(-30 + -10a + (-9a + -3a2) + a2(3 + a)) = 0
(-30 + -10a + -9a + -3a2 + (3 * a2 + a * a2)) = 0
(-30 + -10a + -9a + -3a2 + (3a2 + a3)) = 0

Combine like terms: -10a + -9a = -19a
(-30 + -19a + -3a2 + 3a2 + a3) = 0

Combine like terms: -3a2 + 3a2 = 0
(-30 + -19a + 0 + a3) = 0
(-30 + -19a + a3) = 0

Solving
-30 + -19a + a3 = 0

Solving for variable 'a'.

The solution to this equation could not be determined.

See similar equations:

| 5t-4=44-t | | 3x^4/12x^2 | | -1/3y-4-7 | | Radx+5-radx-1=2 | | 9z+15=8z+12 | | Sinxcosy=7x^2 | | 5x+10=8x+10 | | 15=8-(z+10) | | 42/4a=4 | | 3m-2/3=211/3 | | 6x-1=11+5 | | X-3=3+3x | | 4/5p=3 | | -5(3+r)=30 | | -6.8+4.24=x | | y=1/3x1-2 | | 6(x+3)+8=-16 | | 28x+x+25*32= | | 3t-14t-4=18 | | (3x+5)(2x-1)=x(6x+1)-16 | | x=40.8 | | 20x-7=5+17x | | 7+2p=x | | 7+2p= | | xy+18=32 | | 8x-16=12x+32 | | 28x+x+25= | | 7x+3(4x-13)=189 | | 28x+x= | | 0.11x+0.12(900-x)=100 | | x+4y=23 | | 3x^3-21x^2-24x=0 |

Equations solver categories